Optimizing Fashion Marketing Strategies: Understanding Consumer Behavior in Bangladesh - Barat, Imranur; Md. Mazedul Haque (Indonesian Journal of Business Analytics, 2024)
This study delves into the intricate dynamics of consumer behavior in the context of fashion apparel, focusing on t-shirts and denim pants in Bangladesh. Consumer preferences, perceptions, and purchasing decisions are explored through qualitative research methods, aiming to uncover insights crucial for marketers and retailers. The research emphasizes the significance of fashion attributes such as quality, comfort, fabric, color, and special effects in influencing consumer choices. A sample of 500 young Bangladeshi consumers participated in structured interviews, providing nuanced perspectives on their preferences and expectations. Findings highlight a strong preference for quality and comfort in both t-shirts and denim pants, with significant variations in color and fabric choices. The study underscores the evolving nature of consumer behavior influenced by globalization and digital advancements, posing challenges and opportunities for fashion marketers. By understanding these dynamics, stakeholders can optimize marketing strategies to better meet consumer demands and foster brand loyalty in a competitive marketplace.